Intraspecific Variations in Biology and Pathogenesis of Two Eimeria maxima Isolates From Distinct Geographic Locations - Elham Sobhani; Fatemeh Arabkhazaeli; Seyed Ahmad Madani (Veterinary Medicine and Science)
ABSTRACT Eimeria maxima is one of the seven Eimeria species that infect poultry. Despite being highly immunogenic, this species also displays variability in terms of antigenic characteristics. The objective of this study was to examine the biopathological properties of two distinct Eimeria maxima isolates in Iran. Two mixed field samples, collected from backyard poultry droppings with the highest numbers of Eimeria maxima oocysts, were selected for experimental challenges. The birds were inoculated with an equal number of oocysts, and the biopathological indicators of Eimeria oocysts were evaluated. The findings revealed that the two strains exhibited differences in terms of pathological lesions and intestinal inflammatory reactions on the seventh day post‐challenge (p > 0.05). Consequently, it was demonstrated that Eimeria maxima isolates from geographically distant regions possessed biological and pathogenic dissimilarities.